2020
DOI: 10.1080/17531055.2020.1832292
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian spill-over: the expansion of hybrid humanitarian governance from camps to refugee hosting societies in East Africa

Abstract: The impact and effects of protracted refugee camps on their host environments in East Africa has been the subject of much academic attention since the late 1990s. Such camps are often viewed as exclusionary spaces that isolate refugees from their host societies. Recent analyses, however, posit such camps as hybrid spaces, with fluid boundaries, that provide socio-economic opportunities and are potential drivers of development. Less thinking has gone into how forms of (humanitarian) governance emanate from such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Firstly, scholars have suggested that when large influxes of refugees occur, there is a type of “humanitarian spill over” that can both positively and negatively affect host communities [ 23 , 24 ]. Our study supports this theory given the significant utilization of surgical services in Nyarugusu refugee camp by Tanzanians.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, scholars have suggested that when large influxes of refugees occur, there is a type of “humanitarian spill over” that can both positively and negatively affect host communities [ 23 , 24 ]. Our study supports this theory given the significant utilization of surgical services in Nyarugusu refugee camp by Tanzanians.…”
Section: Discussionmentioning
confidence: 99%
“…The current approach to refugee management heavily relies on ensuring they are encamped, and given their basic needs. This is an ongoing policy both in Kenya and other East African countries (Jansen, B. J. & de Bruijne, 2020) This formula stunts their development, and as a result, it is necessary to review this strategy with not only the aim of harnessing talents and skills, ensuring refugee self-reliance, but also integration and socio-economic inclusion for refugees, and the benefits such a position would bring to the host community and the host country, Kenya as a whole (Alix-Garcia et al, 2018;Betts, 2021).…”
Section: The Concept Of Refugee Entrepreneurshipmentioning
confidence: 99%